Bidenichthys okamotoi, a New Species of the Bythitidae (Ophidiiformes, Teleostei) from the Koko Seamount, Central North Pacific - Peter R. Møller; Werner W. Schwarzhans; Henrik Lauridsen; Jørgen G. Nielsen (Journal of Marine Science and Engineering, 2021)
Two specimens from the Koko Seamount (Koko Guyot), in the Hawaiian-Emperor seamount chain, Central North Pacific, caught in 2009 and 2010 are here described as a new species, Bidenichthys okamotoi. The taxonomy of the species in the genera Bidenichthys Barnard, 1934, and Fiordichthys Paulin, 1995, has been confusing due to the lost type of B. consorbrinus (Hutton, 1876) and the rarity of some of the species. Following the synonymization of Fiordichthys Paulin, 1995, with Bidenichthys by Møller and Nielsen 2015 and of Bidenichthys beeblebroxi Paulin, 1995, with Bidenichthys consobrinus Hutton, 1876, the genus Bidenichthys now comprises five species: B. capensis, B. consobrinus, B. okamotoi, B. paxtoni and B. slartibartfasti. Bidenichthys okamotoi differs from its congeners in, e.g., the fewer precaudal vertebrae (12 vs. 13), more palatine teeth rows (4–6 vs. 2–3), shorter pelvic fins (12.1–13.4% vs. 14.4–21.0% SL), max size (187 vs. 147 mm SL) and the shape of the sulcus of the otolith. We here present an updated diagnosis of the genus. A computed tomography (CT) scan of the holotype of B. okamotoi provides for additional anatomical details. The disjunctive occurrence of Bidenichthys okamotoi on the Emperor Seamount chain about 7500 km from the nearest congeneric taxon in New Zealand is discussed. The fossil otolith-based record of the genus Bidenichthys and its systematic implications is briefly discussed.